MINANG GROOVY - Asadul Haq; Marzam Marzam; Irdhan Epria Darma Putra (FBS Universitas Negeri Padang, 2014)
Abstract This study was animed at promoting the Minangkabau traditional artinto new form of artwork. Through musical work of Minang Groovy, the writer intended to show that the traditional music could be collaborated woth modern music. This,however, also could be developed by using various design and was combined with other modern musical instruments. The traditional music then could be more attractive and enjoyed by all of people especially the young generation. Hence, the traditional music could be more interesting and preserved by the next generation. Kata kunci : komposisi, Minang Groovy, kesenian